KAJIAN MENDALAM TENTANG KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA NON-RUTIN SISWA - Dwi Rizki Muharani; Lalu Sucipto; Syaharuddin Syaharuddin (LPPM Universitas Bina Bangsa, 2023)
This study aims to describe non-routine mathematics problem solving in relation to students' self-efficacy and math anxiety. We collect data from journal databases both national and international. The eligibility criteria are used with the keyword